Digitization and Packaging Innovation Training on SME Rumah Kita: Pelatihan Digitalisasi dan Inovasi Kemasan pada UMKM Rumah Kita - Muhammad Saputra; Yusminar Wahyuningsih; Lisindawati; Niken Paramitasari (LPPM Universitas Yudharta Pasuruan, 2022)
The Covid-19 pandemic has had an impact on change, business people must have the ability to utilize information technology and have the ability to innovate in all aspects including in terms of quality product innovation. Service activities are carried out to conduct training on digitization and packaging innovation for Small and Medium Enterprise (SME) Rumah Kita with the problem of decreasing sales turnover that occurred after the Covid-19 pandemic. The methods used in this service activity are counseling, training, and monitoring or evaluation. As a result of the community service, SME Rumah Kita already has a social media account that can be used as a medium for product promotion and sales. SME Rumah Kita already has a product sales account at an e-commerce shopee. SME Rumah Kita already has more marketable product packaging. SME Rumah Kita already has a sales brand. In addition, quantitative evaluations were measured using pre-test and post-test questionnaires in this community service activity. Based on the results of the pre-test and post-test, showed positive results where each pre-test and post-test on the activities carried out showed an increase in partners' abilities and knowledge related to the service being carried out.